Techniques of Spectrum and Correlation Characteristics for Ultrasonic Ranging System - Tao Gao; Zhen-Jing Yao; Lifeng Zhang (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Both the spectrum and correlation characteristics are important in constructing excitation sequences to realize the multichannel ultrasonic sensors working together. For LFM excitation sequence, there should not be too many simultaneously fired ultrasonic sensors, because of the limited available frequency band of the ultrasonic ranging system. The optimized CFM excitation sequences are proposed to trigger multiple-user ultrasonic sensors in this paper. Comparing with the CFM excitation sequences without optimization, the NSGA-II based optimization CFM excitation sequences are more spectrally matched to the ultrasonic ranging system. Moreover, the ultrasonic crosstalk among multichannel sensors of an ultrasonic ranging system can be eliminated. Real experiments using an ultrasonic ranging system consisting of eight-channel SensComp 600 series electrostatic sensors excited with optimized CFM excitation sequences validate the suitability of the proposed method. The idea of optimizing CFM excitation sequences can also be used for the ultrasonic ranging system which has more than eight ultrasonic sensors. DOI : http://dx.doi.org/10.11591/telkomnika.v12i2.4182